Mewujudkan Ketahanan Keluarga Melalui Pendampingan Literasi dan Perencanaan Keuangan Syariah - Bundo, Mayang; Ulyadi, Ulyadi; Muthmainnah, Ummu; Bahri, Syamsul; Putri, Denesya (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to enhance Islamic financial literacy and family resilience among members of the Majelis Taklim in Balai Gadang Subdistrict by employing the Community Based Participatory Research (CBPR) method. The program evaluation was conducted using pre-test and post-test instruments to measure changes in the level of Islamic financial literacy, family resilience questionnaires, in-depth interviews, and participatory observations to assess participant involvement in activities. Furthermore, data analysis was conducted quantitatively and qualitatively. The results of this program show an increase in family understanding of Islamic financial literacy, the ability to prepare household budgets, and strengthening family resilience. This Islamic-based financial literacy assistance also contributes to improving the quality of life of participants as a whole, covering economic, spiritual, and social dimensions, so that this program can have a positive impact on family resilience.